Bony fishes (Teleostei) caught by small-scale fisheries off central to south coast of São Paulo State, Southeastern Brazil - Motta, Fabio Santos; Rosa, Marcos Rogério; Namora, Rafael Cabrera; Gadig, Otto Bismarck Fazzano [UNESP] (Instituto Virtual da Biodiversidade | BIOTA - FAPESP, 2014)
Small-scale fisheries have a great socioeconomic importance in Brazil. Different regional characteristics along the coast, mostly related to landing sites, equipment used, and targeted species, renders its assessment and monitoring difficult. The aim of this paper is to present a list of species of bony fishes (Teleostei) caught by artisanal fisheries along the São Paulo coast, southeastern Brazil and to provide comments on the relative abundance and conservation status of those species. A total of 315 fishing fleet landings were surveyed, and 106 species distributed among 38 families were recorded. Sciaenidae and Carangidae were the most frequent families in species number. The southern king weakfish, Macrodon atricauda, was the most abundant species, representing 28.03% of the total number of specimens caught. Eleven of the most abundant species are classified as Overexploited in the country or as Near Threatened in the state of São Paulo. These findings reinforce the relevance of assessing and managing artisanal fisheries.

A pesca de pequena escala tem uma grande importância socioeconômica no Brasil. Diferenças regionais ao longo da costa, relacionadas principalmente aos locais de desembarque, artes de pesca e espécies- alvo tornam a sua avaliação e monitoramento difíceis. O objetivo do presente estudo foi apresentar uma lista das espécies de peixes ósseos capturadas pela pesca artesanal na costa de São Paulo, sudeste do Brasil, com comentários sobre a sua abundância relativa e estado de conservação. Foram monitorados 315 desembarques da frota pesqueira, registrando 106 espécies, distribuídas em 38 famílias. As famílias Sciaenidae e Carangidae foram as mais representativas em número de espécies. A pescada amarela, Macrodon atricauda, foi a espécie mais abundante, correspondendo a 28,03% do número total de peixes capturados. Onze das espécies mais abundantes são classificadas como Sobre-explotadas no país ou Próximo de Ameaça de Extinção no estado de São Paulo. Esses resultados reforçam a relevância de avaliar e manejar as pescarias artesanais.
Peixes ósseos (Teleostei) capturados pela pesca de pequena escala na costa centro-sul de São Paulo, Sudeste do Brasil
Keywords: artisanal fisheries; ichthyofauna; species list; western Atlantic; pesca artesanal; ictiofauna; lista de espécies; Atlântico Ocidental